This seems fishy: Technology-Critical Elements as a growing concern to aquatic biota and elasmobranchs in particular - Hauser-Davis, Rachel Ann (Frontiers in Ocean Sustainability, 2023)
Human activities have significantly impacted our natural environments, resulting in extensive degradation, with chemical contamination emerging as a critical concern. This type of pollution has far-reaching implications, affecting ecological health and socioeconomic dimensions. The concept of "contaminants of emerging concern" encompasses newly recognized environmental pollutants, highlighting their diverse and often understudied effects. This category includes microplastics, antibiotics, pharmaceuticals, and metals, among others, many of which lack adequate regulations and understanding of their ecological and human impacts. A subset of these pollutants, termed Technology-Critical Elements (TCEs), holds significance in high-tech industries but also poses environmental challenges due to increased extraction, manufacturing, and disposal. Aquatic environments, the ultimate chemical contaminant sinks, require heightened attention with regard to TCE dynamics and effects. Despite increasing research on TCEs in various aquatic taxa, a lack of comprehensive data hinders further knowledge assessments. In this scenario, fish, key environmental health indicators and links to human contamination, demand focused studies. Cartilaginous fish, specifically, are often overlooked, although ecologically and economically significant, warranting research into TCE effects. This type of research displays the potential to shed light on TCE dynamics, ecological outcomes, and guide conservation strategies for these species and their habitat, also aligning with the One Health concept, acknowledging the interconnectedness of humans, animals, and the environment and contributing to SDG goals, underpinning marine ecosystem conservation.